Utilization Of Leucaena And Sesbania Leaf Meals As Protein Supplements In Broiler Ration - Khan, MKA; Akbar, MA; Khaleduzzaman, ABM; Rahman, MM (Bangladesh Journal of Animal Science, 2012)
One hundred twenty, two weeks old ISA Vedette broiler chicks were randomly allotted to four dietary treatments to investigate the effect of replacing fishmeal with two unconventional sources of leaf meals. The chicks were distributed into dietary treatments A (control-12% CP from fish meal), B (5% CP of fish meal replaced by Leucaena), C (5% CP of fish meal replaced by Sesbania) and D (2.5% CP of fish meal by Leucaena + 2.5% CP of fish meal by Sesbania) having three replications in each treatment group having 10 chicks in each replication. The results showed that Leucaena and Sesbania could be well utilized in broiler ration with no deleterious effects. Replacement of CP at 5% level by Sesbania leaf meal was slightly superior to that of Leucaena or a mixture of Sesbania and Leucaena in respect of broiler performance. Profit per kg live weight gain and per kg dressing yield at 5% level of CP replaced by Sesbania were only slightly superior over 12% CP from fish meal, 5% level of CP from Leucaena or a mixture of two leaf meals respectively. The findings also revealed that Leucaena and Sesbania leaf meals might replace individually or mixture of two leaf meals at 5% level of CP of fish meal for broiler production without affecting performance. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9921 BJAS 2009; 38(1-2): 123-131